2022
DOI: 10.3390/cancers14153639
|View full text |Cite
|
Sign up to set email alerts
|

The Long and Winding Road: An Overview of the Immunological Landscape of Intracranial Meningiomas

Abstract: The role of immunotherapy is gaining ever-increasing interest in the neuro-oncological field, and this is also expanding to the management of intracranial meningioma. Meningiomas are still the most common primary adult tumor of the CNS, and even though surgery and/or radiotherapy still represent cornerstones of their treatment, recent findings strongly support the potential role of specific immune infiltrate cells, their features and genomics, for the application of personalized treatments and prognostic impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Stronger inflammatory responses might be observed in those MSWM cases with both an irregular shape and an increased MIB-1 index compared with those MSWMs that exhibit a significantly lower proportion of cellular components of the monocytic cell lineage. Immune cell infiltration is a key feature of meningiomas, with up to 30% of the cells being immune cells, which makes the meningioma microenvironment a complex landscape of interactions between tumor and immune cells [ 69 , 70 ]. Previous studies have demonstrated an association between shape and PFS in meningiomas, but this is the first report linking increased MIB-1 labeling index to postoperative cranial nerve functioning [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stronger inflammatory responses might be observed in those MSWM cases with both an irregular shape and an increased MIB-1 index compared with those MSWMs that exhibit a significantly lower proportion of cellular components of the monocytic cell lineage. Immune cell infiltration is a key feature of meningiomas, with up to 30% of the cells being immune cells, which makes the meningioma microenvironment a complex landscape of interactions between tumor and immune cells [ 69 , 70 ]. Previous studies have demonstrated an association between shape and PFS in meningiomas, but this is the first report linking increased MIB-1 labeling index to postoperative cranial nerve functioning [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this advantage has not yet been demonstrated in the neurooncological field. The study of this aspect, and for as concerns meningiomas as well, is generating significant interest 82 for a better understanding of the immunological and genomic characteristics of the tumor immune cells infiltrating can provide applications for the development of potentially more personalized treatments. Interferon‐α (IFN‐α) belongs to a family of proteins which are physiologically produced by the cells of the immune system; in addition to antiviral, antiproliferative, and immunomodulatory activity, it is able to activate some intracellular pathways that impact cell growth and division, as well as to modulate various activities of the immune system 83 .…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…The composition and influence of meningioma's tumor microenvironment are not fully understood. Infiltration of immune cells and their polarization toward pro-tumor phenotypes are observed in higher-grade tumors (II and III) ( 17 , 18 ). In this context, studying cytokines can be of great value, particularly those that attract the cells of the immune system and those related to the immunosuppression ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%